Anticipatory grief and ecclesiastical heritage: The demolition of modernist churches in Finland - Immonen, Visa; Hakkarainen, Niko; Sivula, Anna (ISCTE, Instituto Universitário de Lisboa (NIPC 501 510 184), com financiamento da Fundação para a Ciência e a Tecnologia., 2026)
An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.An increasing number of modernist churches of the Evangelical Lutheran Church of Finland which were built in the 1960s and 1970s are reaching a point in their life cycle where they require extensive renovations or demolition. As church membership is falling due to secularisation, an ageing population, and immigration, the financial resources to do extensive renovations are also diminishing. Hence more and more modernist churches are threatened by demolition. Despite their relatively young age, these churches have already become meaningful for and entwined with the lives of local communities, and their removal is felt as a loss of valuable heritage. This article discusses the reasons for demolition and analyses subsequent debates in the public media. While most media attention is directed to values defined by architects and heritage professionals, the emotional and autobiographical values of the locals are less appreciated. It is argued that heritage professionals could prepare for the demolitions by adopting the framework of anticipatory grief, which acknowledges and perhaps alleviates the loss felt by the stakeholders.